Philanthropy in the world's traditions - Ilchman, Warren Frederick; Katz, Stanley Nider; Queen, Edward L. (Indiana University Press, 1998)
An investigation of how cultures outside the Western tradition understand philanthropy and how people in these cultures attempt to realize "the good" through giving and serving. These essays study philanthropy in Buddhist, Islamic, Hindu, Jewish, and Native American religious traditions and in cultures from Latin America, Eastern Europe, the Middle East, Africa, and Asia.
Keywords: Charities -- Cross-cultural studies.; Charities -- History -- Cross-cultural studies.; Social service -- Cross-cultural studies.; Social service -- History -- Cross-cultural studies.; Social service -- Religious aspects.; Service social -- Études transculturelles.; Service social -- Histoire -- Études transculturelles.; Service social -- Aspect religieux.; SOCIAL SCIENCE -- Philanthropy & Charity.; Charities; Social service; Social service -- Religious aspects; Liefdadigheid.; Cross-cultural studies; History